N-heterocyclic organic electrode material, preparation method thereof and aqueous aluminum ion battery

Traditional organic materials are solved by using N-heterocyclic organic electrode materials prepared from 1,10-o-diazaphenyl-5,6-dione and 3,4-diaminobenzonitrile on the positive electrode of the aluminum battery. The restriction of active sites and structural instability on aluminum batteries achieves high specific capacity and good electrochemical performance, which is suitable for large-scale electrochemical energy storage applications.

CN119241544APending Publication Date: 2025-01-03ANHUI UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411775888.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Due to the limitation of active sites, structural instability and redox kinetics, traditional organic electrode materials are difficult to meet the needs of large-scale electrochemical energy storage applications on the positive electrode of aluminum battery.

Method used

N-hex with electron-absorbent-5,6-dione and 3,4-diaminobenzonitrile in ethanol/acetic acid solution were prepared by a one-step dehydration and condensation reaction of 1,10-o-diazaphenyl-5,6-dione and 3,4-diaminobenzonitrile in ethanol/acetic acid solution. Ring organic electrode material improves charge transfer and thermodynamic stability between molecules.

Benefits of technology

The organic electrode material exhibits rapid redox kinetics and excellent electrochemical cycle stability, which is suitable for large-scale promotion, and is simple in preparation process and low in cost, making it suitable for green applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241544A_ABST
    Figure CN119241544A_ABST
Patent Text Reader

Abstract

The invention discloses an N-heterocyclic organic electrode material, a preparation method thereof and a water-based aluminum ion battery, and relates to the technical field of batteries, and the N-heterocyclic organic electrode material is a small molecule containing C = N and-CN active units synthesized through a dehydration condensation reaction. The invention also provides a preparation method of the N-heterocyclic organic electrode material and a water-based aluminum ion battery prepared from the N-heterocyclic organic electrode material. The raw materials used in the invention are green and environment-friendly, the price is low, the preparation process is simple, and the application prospect is good. And when the organic electrode material is used for manufacturing the positive electrode of the aluminum ion battery, the positive electrode has excellent specific capacity, good rate capability and outstanding long cycle stability, so that the aqueous aluminum ion battery has excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to an N-heterocyclic organic electrode material and a preparation method thereof, and an aqueous aluminum ion battery. Background Art

[0002] Due to the characteristics of high safety, greenness and environmental protection, aqueous metal ion batteries have received more attention at present.

[0003] According to the known situation, aluminum metal content currently ranks first among metals, and rechargeable aluminum ion batteries (AIBs) have high theoretical capacity and Al 3+ / Al has a favorable potential, so it also gives it a huge large-scale energy storage capacity. And aluminum ion batteries are highly safe, so aluminum ion batteries have excellent application prospects.

[0004] At present, electrode materials are divided into organic electrode materials and inorganic electrode materials. Inorganic electrode materials have the characteristics of high specific capacity, but they have the problems of limited resources and easy structural collapse. In addition, the huge application market also poses major challenges to the sustainability and cost of inorganic electrode materials (especially positive electrode materials). Organic electrode materials are rich in carbon, hydrogen, oxygen and other elements and can be prepared on a large scale by chemical synthesis. Compared with inorganic materials, organic compounds have many advantages in low cost, structural diversity, design flexibility and meeting sustainable development requirements. Organic electrode materials with high specific capacity can be synthesized through molecular structure design, thus breaking through the energy density limitations of traditional inorganic materials. In addition, compared with inorganic materials, organic materials can also adapt to different battery systems by adjusting functional groups and customizing molecular structures and are not restricted by charge carrier selection. Therefore, aluminum batteries using organic electrode materials provide an attractive path for sustainable and large-scale energy storage.

[0005] Previous studies have shown that the materials used in aluminum battery positive electrodes need to consider the following factors: 1. Whether the electrochemical performance indicators of the material, such as energy density, power density and cycle life, can meet the requirements of practical applications.

[0006] 2. What are the cost, resource availability, and thermal / chemical stability of electrode materials for large-scale electrochemical energy storage applications?

[0007] However, traditional organic materials cannot meet the above requirements well due to their limited active sites, structural instability and slow redox kinetics. That is, the application of traditional organic materials in the positive electrode of aluminum batteries has great limitations and is difficult to promote and apply on a large scale. Summary of the invention

[0008] The invention discloses an N-heterocyclic organic electrode material and a preparation method thereof and an aqueous aluminum ion battery, which can solve the problem that traditional organic materials are greatly restricted when applied to the positive electrode of aluminum batteries due to defects such as limited active sites, structural instability and redox kinetics.

[0009] The technical solution adopted by the present invention is as follows: One of the purposes of the present invention is to provide an N-heterocyclic organic electrode material, the molecular structure of which is: .

[0010] The second object of the present invention is to provide a method for preparing the above-mentioned N-heterocyclic organic electrode material, which is obtained by a one-step dehydration condensation reaction of 1,10-phenanthroline-5,6-dione and 3,4-diaminobenzonitrile.

[0011] Specifically, the specific process of the one-step dehydration condensation reaction is as follows: Step 1: adding 1,10-phenanthroline-5,6-dione and 3,4-diaminobenzonitrile to an ethanol / acetic acid solution with a volume ratio of 1:1, and ultrasonically treating until the solid matter is completely dissolved to obtain a mixed solution; the mass ratio of the 1,10-phenanthroline-5,6-dione to 3,4-diaminobenzonitrile is 195-210:110-130; Step 2: Stir and heat the mixed solution to allow 1,10-phenanthroline-5,6-dione and 3,4-diaminobenzonitrile to react completely, and then cool to room temperature; Step 3: The solution obtained in step 2 is filtered to obtain the target solid, which is then washed and dried to obtain the N-heterocyclic organic electrode material.

[0012] Furthermore, in step 2, the reaction conditions are 70-80° C. and 250-300 rpm.

[0013] Specifically, in step 3, after the suction filtration treatment, the target solid is washed with ethanol, acetic acid and deionized water in sequence.

[0014] The third object of the present invention is to provide an aqueous aluminum ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode is made of the above-mentioned N-heterocyclic organic electrode material.

[0015] Specifically, the preparation process of the positive electrode is as follows: Step a: mixing an N-heterocyclic organic electrode material, a conductive agent and a binder in a weight ratio of 6:3:1, and dispersing them into a uniform solution using N-methylpyrrolidone; Step b: evenly coat the solution on the titanium foil current collector and then dry it to obtain the positive electrode.

[0016] Preferably, the conductive agent is Ketjen black.

[0017] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) 1,10-phenanthroline-5,6-dione is mainly used to prepare molecules with specific functions, synthesize drug precursors, catalytic reaction materials, etc. Because it contains two pyridine ligands, 1,10-phenanthroline-5,6-dione can form stable complexes with a variety of transition metals. These metal complexes can act as catalysts in chemical reactions to promote specific transformation processes. The present invention utilizes the above-mentioned properties of 1,10-phenanthroline-5,6-dione and applies it to organic electrode materials. The present invention designs the component ratio and reaction parameters to allow 1,10-phenanthroline-5,6-dione and 3,4-diaminobenzonitrile to undergo a one-step dehydration condensation reaction in a strongly polar organic solvent, thereby constructing an N-heterocyclic organic electrode material.

[0018] The electron-withdrawing group (-CN) is introduced into the structure of the organic electrode material constructed by the present invention, which reduces the energy gap, thereby promoting the charge transfer between molecules and showing fast redox kinetics; and based on the structural characteristics of the N-heterocycle, strong hydrogen bonds and pp interactions can be formed between the molecules in the organic electrode material, thereby improving the thermodynamic stability. Therefore, when the organic electrode material is used as the positive electrode material of the aluminum ion battery, both the -CN and C=N groups serve as reaction active sites, and both active sites can participate in the reaction, thereby improving the battery specific capacity, so that the aqueous aluminum ion battery has excellent electrochemical cycle stability and rate performance.

[0019] (2) The organic electrode material prepared by the present invention is not only low in raw material cost and environmentally friendly, but also prepared by a one-step dehydration condensation reaction technology, which has a simple preparation process, does not require multiple purifications, and ensures high purity and structural consistency of the product. Therefore, the present invention provides a feasible strategy for realizing the green and low-cost application of organic materials in aluminum ion batteries, which has a very good application prospect and is very suitable for large-scale promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic diagram of the synthesis of the N-heterocyclic organic electrode material obtained in Example 1 of the present invention.

[0021] Figure 2 The charge and discharge curves of the N-heterocyclic organic electrode material obtained in Example 1 of the present invention at different current densities are shown.

[0022] Figure 3 This is the X-ray photoelectron spectrum of the N-heterocyclic organic electrode material obtained in Example 1 of the present invention.

[0023] Figure 4 This is the Fourier transform infrared spectrum of the N-heterocyclic organic electrode material obtained in Example 1 of the present invention and the two monomers for synthesizing the material.

[0024] Figure 5 This is a thermogravimetric analysis curve of the N-heterocyclic organic electrode material obtained in Example 1 of the present invention.

[0025] Figure 6 The aluminum ion battery obtained in Example 3 of the present invention is -1 Long cycle curves at different current densities.

[0026] Figure 7 This is a rate performance diagram of the aluminum ion battery obtained in Example 3 of the present invention at different current densities.

[0027] Figure 8 This is the electrochemical impedance diagram of the aluminum ion battery obtained in Example 3 of the present invention.

[0028] Fig. 9 GITT curve diagram of the aluminum ion battery in Example 3 of the present invention under different charge and discharge conditions. DETAILED DESCRIPTION

[0029] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with various embodiments.

[0030] Example 1

[0031] This embodiment provides an N-heterocyclic organic electrode material (DPPZ-CN), which is obtained by a one-step dehydration condensation reaction of 1,10-phenanthroline-5,6-dione (PHTO) and 3,4-diaminobenzonitrile (DBZ), and its molecular structure is as follows: .

[0032] The preparation process of the N-heterocyclic organic electrode material in this embodiment is as follows: Add 210 mg of 1,10-phenanthroline-5,6-dione and 130 mg of 3,4-diaminobenzonitrile to a 250 mL three-necked flask, then add 75 mL of ethanol / acetic acid (the volume ratio of ethanol to acetic acid is 1:1) solution to the three-necked flask with a 10 mL pipette in batches, and ultrasonicate for 20 minutes until the solid is completely dissolved. Then, place the three-necked flask in an oil bath for stirring and heating. The reaction conditions are 70 °C, 300 rpm, and the reaction time is 12 h. The relevant reaction formula is as follows: Figure 1 shown.

[0033] After the reaction is complete, cool to room temperature, filter, wash with ethanol, acetic acid and deionized water in sequence to obtain the target solid, and finally dry it in a vacuum oven at 80°C for 24 to 30 hours.

[0034] Figure 2 This is the charge and discharge curve of the N-heterocyclic organic electrode material obtained in this example at different current densities. It can be seen that it exhibits a distinct charge and discharge curve and a high specific capacity.

[0035] Figure 3 This is the X-ray photoelectron spectrum (XPS) of the N-heterocyclic organic electrode material obtained in this example. It can be seen that there are C, N and O elements, and the presence of a small amount of oxygen is due to moisture in the air.

[0036] Figure 4 This is the Fourier infrared spectrum of the N-heterocyclic organic electrode material obtained in this example and the two monomers synthesizing the organic electrode material. It can be seen from the infrared spectrum that 2225 cm -1 The peak at 1572 cm corresponds to the cyano group in the molecule, and the disappearance of the amino and carbonyl peaks in the DPPZ-CN molecule compared with the monomer. -1 The retention of the C=N bond at the bottom of the electrode proves the successful synthesis of the organic electrode material.

[0037] Figure 5 This is the thermogravimetric analysis curve of the N-heterocyclic organic electrode material obtained in this example. It can be seen that the thermal decomposition temperature of the organic electrode material is greater than 300° C., indicating that it has good thermal stability.

[0038] Example 2

[0039] The difference from Example 1 is that in this example, 195 mg of 1,10-phenanthroline-5,6-dione and 110 mg of 3,4-diaminobenzonitrile are added to a 250 mL three-necked flask, and then 50 mL of ethanol / acetic acid (volume ratio of 1:1) solution is added to the three-necked flask in portions with a 10 mL pipette, and ultrasonic treatment is performed for 15 minutes until the solid is completely dissolved. Then, the three-necked flask is placed in an oil bath for stirring and heating, and the reaction conditions are 80 ° C, 250 rpm, and the reaction time is 10 h. The remaining steps and parameters are the same as those in Example 1.

[0040] The N-heterocyclic organic electrode material obtained in this example also has a distinct charge-discharge curve, a high specific capacity and good structural thermal stability.

[0041] Example 3 This embodiment provides an aqueous aluminum ion battery, wherein the positive electrode sheet is prepared using the N-heterocyclic organic electrode material (DPPZ-CN) obtained in Example 1, and the specific process is as follows: 1. Preparation of positive electrode sheet: DPPZ-CN, Ketjen black and binder (the weight ratio of the three is 6:3:1) are weighed separately and put into an agate mortar, then 5 ml of N-methylpyrrolidone is added dropwise, and the solution is stirred and dispersed continuously to form a uniform solution, which is then evenly coated on the titanium foil current collector and finally placed in a vacuum oven at 80-100 °C for 18-24 h to make a positive electrode sheet.

[0042] 2. Battery preparation: The positive electrode sheet is used as the positive electrode, the metal aluminum foil is used as the negative electrode, the two electrodes are separated by a glass fiber separator, and an aqueous aluminum perchlorate electrolyte is added to assemble a button battery.

[0043] Figure 6 The aluminum ion battery obtained in this example is 1 A·g -1 Long cycle curve under current density. As can be seen from the figure, after the battery is cycled 1000 times at high current density, the specific capacity is 117.6 mAh g -1 , and has a capacity retention rate of 78%.

[0044] Figure 7 The figure shows the rate performance of the aluminum ion battery obtained in this example at different current densities. It can be seen from the figure that the DPPZ-CN positive electrode material has a high rate performance at current densities of 0.1, 0.2, 0.4, 0.5, 0.7 and 1.0 A·g -1 The results were 208.5, 190.3, 178.2, 165.7, 157.2 and 146.3 mA h·g -1 When the current density is restored to 0.1 A·g -1 When the capacity reaches 194.7 mAh g -1 , indicating that it has good reversibility.

[0045] Figure 8 The electrochemical impedance diagram of the aluminum ion battery obtained in this example is shown in the figure. It can be seen from the figure that the charge transfer impedance (Rct, the semicircle diameter in the high frequency band) of the aluminum ion battery assembled with the organic electrode material is small, indicating that it has a fast charge transfer capability.

[0046] Fig. 9 is the GITT curve of the aluminum ion battery obtained in this example. Therefore, it can be concluded through the calculation formula that under different charge and discharge conditions, the diffusion coefficient of the cation ranges from 10 -10 ~10 -9 cm2 ·s -1 , indicating that the battery has a high ion diffusion rate.

[0047] In summary, the present invention designs an N-heterocyclic organic electrode material, which greatly increases the density of active centers by introducing electron-withdrawing groups (-CN) with redox activity. In addition, the presence of the -CN group can also form strong intermolecular hydrogen bonds and p-p interactions. When the N-heterocyclic organic electrode material is used as a positive electrode material for an aqueous aluminum ion battery, multiple redox active centers enable it to have excellent electrochemical properties. Therefore, compared with the prior art, the present invention has significant technical progress, outstanding substantive features and significant progress.

[0048] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.

Claims

1. An N-heterocyclic organic electrode material, characterized in that: The molecular structure of the organic electrode material is: 。 2. The method for preparing the N-heterocyclic organic electrode material according to claim 1, characterized in that: It is obtained by one-step dehydration condensation reaction of 1,10-phenanthroline-5,6-dione and 3,4-diaminobenzonitrile.

3. The method for preparing an N-heterocyclic organic electrode material according to claim 2, characterized in that: The specific process of the one-step dehydration condensation reaction is as follows: Step 1: adding 1,10-phenanthroline-5,6-dione and 3,4-diaminobenzonitrile to an ethanol / acetic acid solution with a volume ratio of 1:1, and ultrasonically treating until the solid matter is completely dissolved to obtain a mixed solution; the mass ratio of the 1,10-phenanthroline-5,6-dione to 3,4-diaminobenzonitrile is 195-210:110-130; Step 2: Stir and heat the mixed solution to allow 1,10-phenanthroline-5,6-dione and 3,4-diaminobenzonitrile to react completely, and then cool to room temperature; Step 3: The solution obtained in step 2 is filtered to obtain the target solid, which is then washed and dried to obtain the N-heterocyclic organic electrode material.

4. The method for preparing an N-heterocyclic organic electrode material according to claim 3, characterized in that: In the step 2, the reaction conditions are 70-80° C. and 250-300 rpm.

5. The method for preparing an N-heterocyclic organic electrode material according to claim 4, characterized in that: In the step 3, after the suction filtration, the target solid is washed with ethanol, acetic acid and deionized water in sequence.

6. An aqueous aluminum ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The positive electrode is made of the N-heterocyclic organic electrode material according to claim 1.

7. The aqueous aluminum ion battery according to claim 6, characterized in that: The preparation process of the positive electrode is as follows: Step a: mixing an N-heterocyclic organic electrode material, a conductive agent and a binder in a weight ratio of 6:3:1, and dispersing them into a uniform solution using N-methylpyrrolidone; Step b: evenly coat the solution on the titanium foil current collector and then dry it to obtain the positive electrode.

8. The aqueous aluminum ion battery according to claim 7, characterized in that: The conductive agent is Ketjen black.

Citation Information

Patent Citations

  • 5, 10-dialkyl-5, 10-dihydrophenazine polymer as well as preparation method and application thereof

    CN113801255A

  • Carboxyl-containing bipyridino phenazine organic compound as well as preparation method and application thereof

    CN115260196A

  • Organic positive electrode of aluminum ion battery and aluminum ion battery

    CN115911369A

  • Phenazine aqueous positive electrode material and preparation method and application thereof

    CN118406053A

  • N-type organic positive electrode material and preparation method and application thereof

    CN118702694A